Index Selection for in-Memory Databases - Pratham L, Bajaj; Ghotkar, Archana (International Journal of Computer Sciences and Engineering, 2025)
Index recommendation is an active research area in query performance tuning and optimization. Designing efficient indexes is paramount to achieving good database and application performance. In association with database engine, index recommendation technique need to adopt for optimal results. Different searching methods used for Index Selection Problem (ISP) on various databases and resemble knapsack problem and traveling salesman. The query optimizer reliably chooses the most effective indexes in the vast majority of cases. Loss function calculated for every column and probability is assign to column. Experimental results presented to evidence of our contributions.